Aging Yet Independent Women in Elizabeth Gaskell’s Cranford and Charles Dicken’s David Copperfield - Nurulhady, Eta Farmacelia (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
In the Victorian England whose ideal woman was the Angel in the House, a devoted and submissive wife and mother, it would generally be unfortunate for women to be still unmarried past their reproductive years. Using feminist lens, this study compares the Jenkyns sisters (Deborah and Matty) of Elizabeth Gaskell’s Cranford (1853) and Betsy Trotwood of Charles Dicken’s David Copperfield (1850). While aging and single, they are financially independent. Husbandless and childless, the Jenkyns sisters and Betsey could easily fall into the category of redundant women, but they skillfully manage the house and class relations the way the Angels in the House do.